Kolmogorov widths and entropy numbers in the Orlich spaces with the Luxembourg norm - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We obtain the exact-order estimates of the Kolmogorov widths and entropy numbers of unit balls from the binary Besovspaces \$dyad B^{0,γ}_{ p,θ}$ compactly embedded in the exponential Orlich $exp L^{ u}$ spaces equipped with the Luxembourg norm.